PERSEPSI PUSTAKAWAN TENTANG PERMENPAN NOMOR 9 TAHUN 2014 TERHADAP KINERJA PUSTAKAWAN - Suhardini, Dini; Agustina, Susanti (Edulib, 2017)
Functional position is applied for librarians who work in the library of government agency or librarian of Civil State Apparatus. The implementation of functional position is the effort to assign and measure the performance of librarian through the assessment system of work implementation with credit numbers. Librarian as profession and functional position is demanded to have good performance in doing his/her task and function. Librarians perform professional performance in the field of library based on Permenpan Reformasi Birokrasi No. 9 tahun 2014 (Regulation of the Minister of the State Apparatus Utilization and Bureaucratic Reform Number 9 Year 2014). How is the perception of librarian in that regulation? Does this perception influence the implementation of performance standard in library? Both questions are studied by using descriptive quantitative method and the research sample is purposive sampling, which use 14 librarians in central library of Indonesia University of Education. Fifty percent of librarians agree, and 36 % of them very agree that the cluster, task, function, and stage of librarian functional position concretely provide explanation and comprehension in doing their performance. Fifty four percent of respondents significantly agree while 23% of them very agree that their comprehension in the standard of professional performance contributes to the implementation of performance, which includes quality, quantity, and teamwork.